ANALISIS PENGARUH CONTENT MARKETING, BRAND IMAGE, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT UMROH FOODS MEDAN - Lubis, Muthia Amalya; Situmorang, Syafrizal Helmi; Matondang, Nazaruddin (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Social media is an important and essential part of overall marketing and branding, therefore, it must be integrated into any business development or marketing strategy. Social media allows brands to get closer to their customers and potential consumers. In marketing products at PT Umroh Foods Medan, they use several social media, one of which is Facebook, then Instagram, and Google Business. This study aims to analyze the effect of Content Marketing, Brand Image, and Product Quality on Purchasing Decisions at PT Umroh Foods Medan. This research is a quantitative study. The population in this study were consumers who had purchased products at PT Umroh Foods Medan, so the sample used was 160 respondents using purposive sampling techniques. Data collection techniques used questionnaires and literature studies. Data analysis techniques used multiple linear regression analysis, t-test, F-test and coefficient of determination test. The results of this study indicate that Content Marketing has a positive and significant effect on Purchasing Decisions, Brand Image has a positive and significant effect on Purchasing Decisions, Product Quality has a positive and significant effect on Purchasing Decisions, Content Marketing, Brand Image, and Product Quality simultaneously have a positive and significant effect on Purchasing Decisions